Investigation of dominant spin wave modes by domain walls collision - Goolaup, S. (2014)
Spin wave emission due to field-driven domain wall (DW) collision has been investigated numerically and analytically in permalloy nanowires. The spin wave modes generated are diagonally symmetric with respect to the collision point. The non-propagating mode has the highest amplitude along the middle of the width. The frequency of this mode is strongly correlated to the nanowire geometrical dimensions and is independent of the strength of applied field within the range of 0.1 mT to 1 mT. For nanowire with film thickness below 5 nm, a second spin wave harmonic mode is observed. The decay coefficient of the spin wave power suggests that the DWs in a memory device should be at least 300 nm apart for them to be free of interference from the spin waves.